FINANCIAL RESILIENCE AND NPA ANALYSIS OF STATE BANK OF INDIA FOR STRENGTHENED LOCAL SELF-GOVERNANCE (Lex localis - Journal of Local Self-Government, 2025)
This study critically examines the financial health and management efficiency of the State Bank of India (SBI) and its associate banks, emphasizing the implications of Non-Performing Assets (NPAs) on institutional stability and local financial governance. Using secondary data from annual reports, banking bulletins, and official publications, the research employs a robust econometric framework integrating descriptive statistics, multivariate Skewness (Sk), Kurtosis (Ku), correlation, regression, and the Augmented Dickey-Fuller (ADF) unit root test to assess data stationarity. ANOVA tests were used to evaluate interbank performance differences, while Altman’s Z-score model was applied to measure financial resilience. The results revealed that, in several parameters—such as demand deposits, cost of credit, and term loans—there exists both significant and non-significant variations among SBI and its affiliates. Particularly, the ratio of term loans and net NPA as a percentage of total assets indicated notable disparities, affirming the influence of NPA management on overall financial performance. Multiple regression analysis further demonstrated a strong positive relationship (R = 0.998) between current and prior year credit recoveries, indicating consistent recovery performance trends. The study underscores that effective NPA management contributes to strengthening local banking governance and sustainable financial decentralization. These findings offer valuable insights for policymakers, financial regulators, and local government institutions in enhancing the resilience of public sector banks within India’s evolving financial ecosystem.